Rol de enfermería en prevención de complicaciones postoperatorias en cirugía de columna - Paucar Paguay, Mishel Aracely (2025)
Spinal surgery is a time consuming operation with a high risk of postoperative complications, the nursing professional plays an important role in the recovery of every patient post-surgery. The aim of this study is to design an educational programme for the prevention of postoperative complications in patients undergoing spinal surgery. The research had a qualitative approach that was developed through bibliographic reviews of articles and theses found in databases, and the relevance of these was captured by means of a Prisma flow chart. Among the main results, the design of an educational programme helps to contribute to better management by health personnel in the prevention of postoperative complications in patients who have undergone spinal surgery, which emphasises the characterisation of the different types of postoperative complications that can occur here, various infection prevention techniques and management of surgical wounds, as well as the management of respiratory complications. From the above it is concluded that the programme designed to improve the patient's optimal recovery by allowing early identification of signs of complications and by acting in a timely manner to mitigate them.